Nivel de conocimiento y aplicación de medidas de seguridad laboral en los trabajadores de la facultad de agronomía - fundo Zungarococha - Iquitos, Loreto - Perú, 2022 - De Vivanco Oroche, Hector Manuel (2023)
At the Faculty of Agronomy of the National University of the Peruvian Amazon, located on the Zungarococha highway, a study was carried out to measure the level of knowledge and application of occupational safety measures to which workers in all projects and workshops are exposed. of teaching of the Faculty of Agronomy - Zungarococha farm, where the following could be determined: the personnel who work in the Faculty of Agronomy are elderly people, the majority are male, most of them have been serving for a long time , their level of knowledge in occupational health and safety measures of most workers have a medium level of knowledge and their application of safety measures depend on the basic knowledge that each one of them has, where the people with the longest service time and older are those with a lower level of knowledge on occupational health and safety issues and are also the workers who do not apply prevention measures since they have never been trained or previously had an interest in worker safety by the employer, which is the university, it was also determined that the ratio of their average level of knowledge that they possess in occupational health and safety issues and their commitment to apply them, has generated a high level of expectations in occupational health and safety issues, they see that working with the necessary protection equipment allows them to safeguard their physical integrity and the tranquility of their families.